Eixo ECA2/ANG-(1-7)/mas e sua regulação no processo de ovulação - Santos, Joabel Tonellotto dos (2011)
The Renin-Angiotensin System (RAS) has been associated with various reproductive functions, including the ovulatory cascade. Unlike angiotensin II (AngII), the role of angiotensin-(1-7) [Ang-(1-7)] has not been characterized in the ovary of mono-ovulatory species. The objective of this study was to determine the Ang-(1-7) concentration in follicular fluid and Ang-(1-7)-related enzymes and MAS receptor mRNA expression during the ovulatory process in cattle. Forty cows were synchronized and those with follicular diameter ≥ 12 mm received GnRH analog (i.m.) to induce a LH peak and were ovariectomized at different periods (0, 3, 6, 12 and 24 h). Follicular fluid was stored to measure Ang-(1-7). Theca and granulosa cells were collected to evaluate gene expression by RT-qPCR assay. In a second experiment, the effect of Ang-(1-7) and A-779 (MAS receptor inhibitor) on the epiregulin mRNA expression by granulosa cells was evaluated in vitro. In the third experiment, the hypothesis that Ang-(1-7) is essential for ovulation was tested using an in vivo model by injecting A-779 intrafollicularly. Twenty synchronized cows were intrafollicularly injected with A-779 or saline 0.9% (control group) when the follicles reached a diameter of at least 12 mm and were challenged with an IM application of GnRH analogs. The levels of Ang-(1-7) increased in the follicular fluid at 24 h post-treatment (p < 0.05). Messenger RNA expression of MAS, ECA2, NEP and PEP was detected in theca and granulosa cells at all periods after GnRH injection. In granulosa cells, ACE2, NEP and PEP mRNA expression was regulated in different moments after GnRH treatment (p < 0.05). The addition of Ang-(1-7) or A-779 was not able to change the pattern of Ereg mRNA expression in our granulosa cell culture system. The intrafollicular application of A-779 (10-5M) did not block ovulation when performed before the expected peak of LH (100% of cows ovulated in treated and control groups). Differential expression of ACE2, NEP and PEP in granulosa cells and increased concentrations Ang-(1-7) next ovulation may indicate a role of this peptide in ovulation in cattle.